Архітектурне тло ікони покрову пресвятої богородиці з річиці на Волині - Диба, Ю. Р.; Dyba, Yu. (Видавництво Львівської політехніки, 2018)
Проаналізовано реалістичне зображення елементів інтер’єру храму в іконі Покрову Пресвятої Богородиці зламу ХУ-ХУІ ст. з колекції Рівненського краєзнавчого музею, що походить зі Святотроїцької церкви в с. Річиці Зарічненського району Рівненської області. Порівняльною характеристикою архітектурних елементів доведено, що архітектурним прототипом цього зображення слугував Собор святої Софії в Константинополі.

The author investigates realistic image of interior elements, depicted in the icon of “Intercession of the Theotokos”. This icon dates from the end of the 15th - the beginning of the 16th cent, and comes from Volhynian village Richytsia. Now it is stored in the collection of the Rivne Local History Museum. This work is considered to be a classic in Ukrainian late medieval art. The icon is distinguished by its elaborate composition and large groups of characters. In the scientific community there are numerous questions regarding the identification of specific sources of the complex of its architectural elements of this icon. In this regard, many general statements, various interpretations and obvious fantasies arose in the scientific literature. This gives grounds for a more thorough historical -architectural analysis of the notable features of iconography of this image. In the monumental study of Volodymyr Aleksandrovich “Intercession of the Theotokos” an icon from Richytsia is considered in a separate section. A thorough analysis of the experience of studying the icon performed in this work greatly simplifies the work with literature. The researcher drew attention to the most obvious debatable forms of the architectural background of the icon and various interpretations of his integral composition. The identification of the elements of the architectural background of the icon from Richytsia was of interest to all the researchers of this artistic work. Is it possible to link the whole complex of architectural features of this to a particular temple? Such a question is not hopeless. After all, the fullness of the concrete forms of the architectural background of the icon is unique. The originality of the interpretation of all components of the architectural background does not give grounds to consider them as typical. Therefore, the identification of the source (sources?) of their origin will be a logical continuation of the thorough study of the icon. The author argues that the source of the ideological program of the Icon of “Intercession of the Theotokos” is related to Constantinople. However, the facilities of the complex in Blacherna can not serve as a prototype. They do not have the appropriate set of architectural elements, characteristic of the icon. The study shows the fact that the prototype of the architectural background of the investigated icon was the Cathedral of St. Sophia in Constantinople. The most striking element of the architectural background of the icon is the arcade. The four tiers of this arcade are depicted on the background of the figure of the Virgin. The three small domes served rather as signs of a constructive system of overlappings of the Constantinople Temple, which is formed from a massive central dome and two hemispheres. Other elements of the interior are similar. Comparison of such elements proves that the model served Hagia Sophia.
The architectural background of the icon of ’intercession of the theotokos’ from the richytsia
Keywords: Ікона Покрову Пресвятої Богородиці; церква св. Трійці с. Річиця; архітектурне тло ікони; елементи інтер’єру; Собор святої Софії у Константинополі; Icon of the Intercession of the Theotokos; church of St. Trinity from the village Richytsia; architectural background of icon; interior elements; Hagia Sophia in Constantinople; 72.04.033.2